Beneficial effects of switching to denosumab from bisphosphonates or selective estrogen receptor modulators in postmenopausal women with type 2 diabetes and osteopenia/osteoporosis. Issue 7 (13th December 2020) - Miyoshi, Arina; Kameda, Hiraku; Nagai, So; Nakamura, Akinobu; Miya, Aika; Takase, Takahiro; Atsumi, Tatsuya; Miyoshi, Hideaki
Abstract: Aims/Introduction: Patients with type 2 diabetes mellitus have a higher bone fracture risk than patients without diabetes. Although denosumab (Dmab) is a potent bone resorption inhibitor, its efficacy in patients with type 2 diabetes mellitus has not been elucidated. In this study, we investigated the effects of switching to Dmab from bisphosphonates (BP) or a selective estrogen receptor modulator (SERM) in postmenopausal type 2 diabetes mellitus patients. Materials and Methods: This was a three medical institutions, prospective, observational study for postmenopausal patients with type 2 diabetes mellitus whose T‐score of femoral neck or lumbar spine bone mineral density was under −1.0 standard deviation, even after >6 months of BP or SERM administration. After obtaining consent, participants were treated for osteopenia/osteoporosis by either continuing BP (BP‐BP group)/SERM (SERM‐SERM group), or by switching to Dmab (BP‐Dmab or SERM‐Dmab groups). Changes in bone mineral density and bone metabolism marker levels were evaluated after 6 months. Results: A total of 48 patients were included in this study, and each group comprised 12 patients. No significant difference existed in baseline characteristics among the groups. The average age and glycated hemoglobin were 71 ± 8 years and 7.2 ± 0.9%, respectively. In the SERM‐Dmab group, lumbar spine bone mineral density was significantly increased by 5.0% compared with the SERM‐SERM group ( P  < 0.04). Serum bone‐specific alkaline phosphatase and tartrate‐resistant acid phosphatase 5b were significantly decreased in the BP‐Dmab and SERM‐Dmab groups compared with the BP‐BP and SERM‐SERM groups, respectively. Conclusions: Switching to Dmab from BP or SERM is beneficial to prevent osteoporosis progression in postmenopausal patients with type 2 diabetes mellitus patients. Abstract : We showed more favorable effects of denosumab on bone metabolism compared with bisphosphonates or selective estrogen receptor modulator alone in postmenopausal patients with type 2 diabetes mellitus. Switching from bisphosphonates or selective estrogen receptor modulator to denosumab provides an effective treatment strategy to prevent the progression in postmenopausal patients with type 2 diabetes mellitus who are still in the osteopenia or osteoporosis state after treatment with bisphosphonates or selective estrogen receptor modulator and active vitamin D.